2017
DOI: 10.5430/ijhe.v6n3p91
|View full text |Cite
|
Sign up to set email alerts
|

The Group-based Assessment Approach in Nursing Education: The Perspective of Nursing Students on Group-based Assessment Process at a Namibian University

Abstract: Group-based assessments used in the Bachelor of Nursing Science (clinical) Honours programme at a public university in Namibia are usually in the form of assignments and projects. Completing tasks in groups helps students to develop important skills like critical thinking and debating. In addition, it prepares them to work in the health-care environment where collaboration with others is required. That said, nursing students lack cooperation during the process of completing their group assignments or projects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…The findings proved that inclusion group testing in composition writing test had culminated significant positive outcome on enhancing the students' performance in composition writing. Findings supported by the results of the previous studies of Giuliodori et al (2008); Giuliodori et al, (2009) and Nuuyoma (2017) and proved that employing group testing was beneficial for enhancing students' performance. Therefore, the 1 st hypothesis will be accepted that there is a significant statistical difference effect on group testing as a strategy on enhancing the students' performance on writing composition.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The findings proved that inclusion group testing in composition writing test had culminated significant positive outcome on enhancing the students' performance in composition writing. Findings supported by the results of the previous studies of Giuliodori et al (2008); Giuliodori et al, (2009) and Nuuyoma (2017) and proved that employing group testing was beneficial for enhancing students' performance. Therefore, the 1 st hypothesis will be accepted that there is a significant statistical difference effect on group testing as a strategy on enhancing the students' performance on writing composition.…”
Section: Discussionsupporting
confidence: 81%
“…Giuliodori, et al (2008) and Rao et al (2009) discovered that employing group testing was beneficial for enhancing students' performance. In addition, Nuuyoma (2017) indicated that "group-based assessment approach strategy had a very significant effect on learning nursing students as completing tasks in groups which helped students to develop important skills as critical thinking and debate." Geronimo and Rosales (2018) revealed that there were significant increases in the test scores of the students after having group testing in the four quizzes (problem solving) and two major examinations (multiple choice) in General Physics.…”
Section: Review Of the Related Studies In Writing Composition And Gro...mentioning
confidence: 99%
See 1 more Smart Citation
“…Group-based assignments are another TBL form used by many educational establishments, including nursing schools [13,14]. To perform the group assignments, the students in a class are divided into groups by the subject teachers or the students themselves.…”
Section: Introductionmentioning
confidence: 99%
“…A limited number of studies on teaming of nursing students showed nursing students' dislike of teamwork, mainly because of a lack of participation from team members [13,14,16]. Social-cultural influences on teamwork were noted.…”
Section: Introductionmentioning
confidence: 99%